Effect of family member participation nursing on depression of patients with dysphagia (家属参与型护理对吞咽障碍患者抑郁状态的影响) - LI Xia (李侠); JI Danting (纪丹婷); WANG Yingfen (王迎芬); TU Manyu (涂曼玉); ZHANG Meirui (张美瑞) (中西医结合护理)
Objective To investigate the effect of family member participation nursing on depression of patients with dysphagia. Methods A total of 72 patients with dysphagia were selected and divided into control group and intervention group, with 36 cases in each group. The control group was given routine rehabilitation nursing, and the intervention group was given family member participation nursing on the basis of the control group. The nursing ability of family members, depression degree score and quality of life score of the two groups were observed on the first day of hospitalization and one month after intervention. Results After intervention, the Family Caregiver Task Inventory(FCTI) score of family members in intervention group was better than that in control group (P＜0. 01). The Hamilton Depression Scale(HAMD) in the intervention group was lower than that of control group(P＜0. 05), and the Swallow Quality-of-Life Questionnaire (SWAL-QoL)score in the intervention group was higher than that of control group (P＜0. 05). Conclusion Family participation nursing can improve the care ability of family members of patients with dysphagia, improve the depression state and improve the quality of life of patients. (目的 探讨家属参与型护理对吞咽障碍患者抑郁状态的影响。方法 选取2019年8月—2021年8月中国科学院大学深圳医院(光明)收治的吞咽障碍患者72例, 分为对照组和干预组, 各36例。对照组给予常规康复护理, 干预组在对照组基础上增加家属参与型护理。对比观察住院第1天及干预1个月后2组患者家属的照顾能力、患者抑郁程度评分和生活质量评分情况。结果 干预后, 干预组患者家属照护能力量表(FCTI)评分低于对照组, 差异有统计学意义(P＜0. 01)。干预组患者汉密尔顿抑郁量表(HAMD)评分低于对照组, 吞咽障碍生活质量量表(SWAL-QOL)评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 家属参与型护理能提高吞咽障碍患者家属照顾能力和改善抑郁状态, 提升患者生活质量。)